Students' Perceptions of the Strategies Used by Teachers in Teaching Speaking in Desa Bahasa Sragen - Novita Indah Purwaningsih; Agus Wijayanto; Ngadiso Ngadiso (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The objective of this study was to determine students' perceptions of the teaching strategies used by teachers to teach speaking in “Desa Bahasa Sragen”. The subjects of this study were the six students of the “Desa Bahasa Sragen”. There are six students who voluntarily agreed to be participants in this study. The instruments used to gather data was interviews. The case study is used in this research as a research method. The results showed that the students gave a positive perception of the strategies used by the teacher in teaching speaking in “Desa Bahasa Sragen”. They stated that the strategies used by the teacher in teaching speaking in “Desa Bahasa Sragen” could help them practice speaking, making them feel the learning process fun. In addition, their positive perceptions are influenced by the new experiences they get while learning English, especially speaking in “Desa Bahasa Sragen”.